2021
DOI: 10.1097/aud.0000000000001100
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and Word Recognition for Unprocessed and Vocoded Speech Stimuli

Abstract: Objectives: Individuals with cochlear implants (CIs) show reduced word and auditory emotion recognition abilities relative to their peers with normal hearing. Modern CI processing strategies are designed to preserve acoustic cues requisite for word recognition rather than those cues required for accessing other signal information (e.g., talker gender or emotional state). While word recognition is undoubtedly important for communication, the inaccessibility of this additional signal information in speech may le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(135 reference statements)
1
1
0
Order By: Relevance
“…This suggests that to reach recognition threshold in noise, emotional semantics call for an addition of ∼3.3 dB SNR as compared to emotional prosody. This prosodic advantage across age groups expands previous evidence that focused mainly on an accuracy advantage for prosodic recognition over spoken word recognition ( Dupuis and Pichora-Fuller, 2014 ; Morgan, 2021 ; Morgan et al, 2022 ). A noteworthy study by Morgan (2021) reported a 10 dB SNR advantage between emotional prosodic thresholds and spoken word identification thresholds in young adults.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This suggests that to reach recognition threshold in noise, emotional semantics call for an addition of ∼3.3 dB SNR as compared to emotional prosody. This prosodic advantage across age groups expands previous evidence that focused mainly on an accuracy advantage for prosodic recognition over spoken word recognition ( Dupuis and Pichora-Fuller, 2014 ; Morgan, 2021 ; Morgan et al, 2022 ). A noteworthy study by Morgan (2021) reported a 10 dB SNR advantage between emotional prosodic thresholds and spoken word identification thresholds in young adults.…”
Section: Discussionsupporting
confidence: 84%
“…To date, only a few studies have tried to directly compare the recognition of the semantic and prosodic channels, mostly in young adults (but see, Dupuis and Pichora-Fuller, 2014 ). For example, Morgan (2021) showed that sensory thresholds were better for prosodic-emotion recognition than for word recognition in noise for young adults (see also van Zyl and Hanekom, 2011 ; Ritter and Vongpaisal, 2018 ; Morgan et al, 2022 ). However, these studies did not directly measure semantic-emotion recognition, but rather used word/sentence recognition as a placeholder.…”
Section: Discussionmentioning
confidence: 99%